Short-term chloral hydrate as an add-on treatment may improve sleep and alleviate agitation in inpatients with treatment resistant schizophrenia: a retrospective case series study - Shelef, Assaf; Alaa, Habashi; Bloemhof-Bris, Esther; Halperin, Dania; Weizman, Shira; Stryjer, Rafael (Frontiers in Psychiatry, 2024)
Introduction Chloral hydrate (CH), a medication dating back to 1832, is tranquilizer and sleep promoter still used today. It remains an option for short-term insomnia therapy and sedation before medical procedures, despite its controversial safety profile. Methods This study investigated the potential benefits of chloral hydrate addition for increasing sleep duration and reducing agitation and violence in inpatients with treatment-resistant schizophrenia (TRS). A retrospective, observational case series design was utilized, analyzing data from fourteen patients diagnosed with TRS disorders. Results CH addition increased the rate of full night sleep and decreased the rates of agitation and verbal and physical violence events. Notably, no adverse events including falls were reported during CH addition. Discussion CH shows some short-term benefits in improving sleep disorders and reducing violent and agitated behavior in patients with TRS. Our study has limitations due to its small sample size, retrospective design and lack of a control group. A large-scale, double-blind, randomized trial is needed to further explore the efficacy and safety of CH in psychiatric populations with TRS accompanied by agitation, violence and disturbed sleep.